Rock mass rating in Bükk Mts., N Hungary based on petrophysical parameters and parting conditions - Mcintosh , Richard William; Encs, Balázs (Acta Geographica Debrecina Landscape & Environment series, 2016)
In the region of Bánkút and Ómassa, Bükk Mountains the strength of the rocks of 29 outcrops was studied based on Rock Mass Rating (RMR). Strength of the rock masses showed no correlation with the material of the Formations they exposed, however, correlation between the orientation of valleys and ridges and the location of the most deformed rocks and thus that of the rock masses with poorest qualification could be observed.